Does the Interval Between Hysterectomy and Start of Adjuvant Radiation Treatment Influence Survival in Women With Endometrial Carcinoma?: A National Cancer Database analysis. (August 2020) - Ghanem, Ahmed I.; Modh, Ankit; Burmeister, Charlotte; Mahmoud, Omar; Elshaikh, Mohamed A.
Abstract : Objective: The objective of this study was to analyze the impact of the time interval (TI) between hysterectomy and initiation of adjuvant radiation treatment (ART) on overall survival (OS) among women with early stage endometrial carcinoma (EC) using the National Cancer Database (NCDB). Materials and Methods: The NCDB was queried for women with the International Federation of Gynecology and Obstetrics (FIGO) stage I to II EC who underwent hysterectomy followed by ART. We examined the prognostic impact of TI on OS using the cutoff ⩽8 or >8 weeks to initiate radiation treatment (RT). Two groups of patients were created. Kaplan-Meier curves were created for OS analysis. Predictors of OS were identified. Results: A total 16, 520 women were identified. The median follow-up time for the entire cohort was 59.1 months. Median age was 63 years, and 82% were FIGO stage I. Pelvic external beam RT alone was used in 9569 (58%) and vaginal brachytherapy alone in 4265 women (26%). In total, 10, 040 women (61%) received RT ⩽8 weeks. Delay in initiating RT >8 weeks was associated with shorter 5-year OS ( P =0.048). Independent predictors of shorter OS includes older age, African American race, higher comorbidity burden, higher tumor grade, the presence of lymphovascular invasion and stage II tumors. Although TI in initiating RT was a significant predictor for OS in univariate analysis, its independent significance of OS was lost on multivariate analysis ( P =0.28). Conclusion: Our study suggests that TI between hysterectomy and initiation of ART was not an independent predictor of OS in women with early stage EC.